Tourism in Geography Textbooks in Secondary Education and High School: The Case of the Balearic Islands - Miquel Àngel Coll-Ramis; Víctor Picó; Antoni Ordinas (MDPI AG, 2022)
Since the mid-20th century, tourism has become a strategic activity for the economy of the Balearic Islands, causing profound social, territorial, and environmental transformations. This fact challenges local society, which must be aware of its environment to better face the future challenges posed by this economic activity. With this goal, the official curriculum has been analyzed, making it possible to ascertain the approach with which this subject is taught by the administration and what objectives are set. Furthermore, a review was carried out of the contents of geography textbooks in the third year of ESO and the second year of the Baccalaureate, which corresponds to the educational stages in which tourism aspects appear. The results obtained represent a fundamental strategic diagnosis to improve the teaching and learning of this key activity for the Balearic Islands, giving it more importance and adapting its approach to the current times.